Irregularity for Abortion: Canon 1041 - Peters, Edward N. (Roman Replies and CLSA Advisory Opinions 2011, 2011)
"A young man who is considering applying to the seminary disclosed to me, in spiritual direction but outside of confession, that, several years ago, shortly after their having engaged in sexual intercourse, the man's girlfriend demanded that he drive her immediately to an abortion clinic to secure a "morning after pill. " He did so and is certain that the woman took the drug(s) she acquired there, and is likewise sure that the woman did not later have a child that could be his. Three questions: (1) has this man incurred the irregularity of abortion under canon 1041, 4°; (2) even if he has not, should he still disclose this matter to his bishop; (3) would I be obligated in any way to bring this matter to the attention of the man's bishop?"